Resiko Kerentanan Masyarakat Perkotaan Terhadap Bahaya Banjir di Kelurahan Margagiri, Kecamatan Bojonegara, Kabupaten Serang - Arta Rusidarma Putra; S Silfiana (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2020)
This study aims to analyze the socio-economic, and physical vulnerability of urban communities to flood disasters in Margagiri Village, Bojonegara District, Serang Regency, Banten Province with quantitative descriptive methods and spatial analysis. The data used are primary data obtained from the results of structured observations and interviews with questionnaires and secondary data obtained from various documents and related and competent agencies. Samples were taken by simple random sampling method, as many as 90 households from 483 existing populations. The results of the study explained that based on the interpolation results of flood depths affected by flooding were in most of the eastern region of the study with a maximum depth of 1.5 meters caused by several factors including lower topographic conditions, river narrowing, blocked drainage and dirty river channels. obstructing the flow of the river that flows to the main outlet. The results also found that higher socio-economic vulnerability was found at the level of education, most of which were low levels of education, namely elementary school (SD) (40.42%) and elements of the population vulnerable to old age and children by 30.09%. Other research findings are the level of physical vulnerability of high buildings found as many as 32 buildings, moderate physical vulnerability of 43 buildings, and low vulnerability of 25 buildings. The level of vulnerability is moderate to high dominated by non-wall building types